2012
DOI: 10.3109/0886022x.2012.708378
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Acute Peritoneal Dialysis Treatment in Neonatal Period

Abstract: The aim of this retrospective study was to evaluate our neonatal intensive care unit (NICU) patients' characteristics treated with acute peritoneal dialysis (PD) and their risk factors for mortality. We also wanted to share our experience of the application of PD in neonates who required less than 60 mL of dwell volume and their PD-related problems, as well as special solutions for these problems. This study included 27 infants treated in our NICU between February 2008 and December 2011. We retrospectively ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 13 publications
0
49
0
5
Order By: Relevance
“…This may be due to differences in the studies' sample sizes. 15 Other studies have reported that renal damage 16,17 and congenital defects 18 are associated with mortality; the latter is the second cause of neonatal mortality in developed countries. The intervention of the health team should improve the prognostics for these illnesses and, therefore, early treatment, optimized transport time and an Intra-hospital mortality among neonates 573 interdisciplinary (prenatal) approach can improve outcome for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to differences in the studies' sample sizes. 15 Other studies have reported that renal damage 16,17 and congenital defects 18 are associated with mortality; the latter is the second cause of neonatal mortality in developed countries. The intervention of the health team should improve the prognostics for these illnesses and, therefore, early treatment, optimized transport time and an Intra-hospital mortality among neonates 573 interdisciplinary (prenatal) approach can improve outcome for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…90 If peritoneal dialysis is felt to be a short-term requirement, a temporary catheter can be placed. Several studies describe successful peritoneal dialysis by several different techniques in critically ill neonates as small as 830 g. [91][92][93][94][95] When PD is technically difficult because of abdominal wall defects, skin infections, communication to the pleural space, or high ultrafiltration needs, CRRT can be performed. CRRT is performed with a hemodialysis catheter placed in a central location and either regional or systemic anticoagulation.…”
Section: Neonatal Cardiac Surgerymentioning
confidence: 99%
“…Over the years, PD has become an effective and increasingly popular alternative to HD in the management of critically ill neonates, including premature infants [9,25]. PD has been relatively safe, technically simple, and cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…PD has been relatively safe, technically simple, and cost-effective. It can also be applied in hemodynamically unstable premature infants [2,8,12,25]. The catheter design, implantation site, and system configuration used to perform dialysis determine the effectiveness of PD in premature infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation